2014
DOI: 10.3892/or.2014.2983
|View full text |Cite
|
Sign up to set email alerts
|

miR-186, miR-3651 and miR-494: Potential biomarkers for oral squamous cell carcinoma extracted from whole blood

Abstract: microRNAs (miRNAs) are aberrantly expressed in the whole blood of patients suffering from different types of cancer. Collection of whole blood samples is a minimally invasive procedure. To date, little is known concerning the altered miRNA expression in patients suffering from oral squamous cell carcinoma (OSCC). The present study aimed to evaluate the difference in miRNA expression in whole blood samples in OSCC patients as compared to healthy volunteers who served as controls. In 20 blood samples from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 44 publications
5
55
1
Order By: Relevance
“…Researcher have explored whether circulating miRNAs could be used as potential molecular biomarkers for diseases including human malignancies. Also, studies suggest that differentially expressed miRNA are present in tumor tissues or whole blood of OSCC patients, but few reports described serum miRNAs [9,10]. Thus, we studied 26 differently expressed serum miRNAs from OSCC patients and confirmed that miR-483-5p was significantly correlated with tumor lymph nodal metastases and tumor differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…Researcher have explored whether circulating miRNAs could be used as potential molecular biomarkers for diseases including human malignancies. Also, studies suggest that differentially expressed miRNA are present in tumor tissues or whole blood of OSCC patients, but few reports described serum miRNAs [9,10]. Thus, we studied 26 differently expressed serum miRNAs from OSCC patients and confirmed that miR-483-5p was significantly correlated with tumor lymph nodal metastases and tumor differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…In gastrointestinal stromal tumor cells, lung cancer cells (12), medulloblastoma cells (21), oral cancer cells (22), esophageal squamous cell carcinoma cells (23), gastric cancer (24) and cholangiocarcinoma (21), miR-494 functions as a tumor suppressor gene. By contrast, in glioma cells, oral squamous cell carcinoma (25), bronchial cancer (26) and hepatocellular carcinoma (15), miR-494 functions as an oncogene. In the present study, the expression profile of miR-494 was evaluated in 25 pairs of tumor and adjacent non-tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…The level of miR-494 was higher in a number of cancers such as classical Hodgkin's lymphoma [4] and oral squamous cell carcinoma [5]. Anti-miR-494 treatment significantly diminished tumor size in mice with primary myc-driven liver tumor [6].…”
Section: Introductionmentioning
confidence: 99%